Human papillomavirus 16 oncoprotein E7 stimulates UBF1-mediated rDNA gene transcription, inhibiting a p53-independent activity of p14ARF. - Isabelle Dichamp; Paule Séité; Gérard Agius; Alice Barbarin; Agnès Beby-Defaux (PLoS ONE)
High-risk human papillomavirus oncoproteins E6 and E7 play a major role in HPV-related cancers. One of the main functions of E7 is the degradation of pRb, while E6 promotes the degradation of p53, inactivating the p14ARF-p53 pathway. pRb and p14ARF can repress ribosomal DNA (rDNA) transcription in part by targeting the Upstream Binding Factor 1 (UBF1), a key factor in the activation of RNA polymerase I machinery. We showed, through ectopic expression and siRNA silencing of p14ARF and/or E7, that E7 stimulates UBF1-mediated rDNA gene transcription, partly because of increased levels of phosphorylated UBF1, preventing the inhibitory function of p14ARF. Unexpectedly, activation of rDNA gene transcription was higher in cells co-expressing p14ARF and E7, compared to cells expressing E7 alone. We did not find a difference in P-UBF1 levels that could explain this data. However, p14ARF expression induced E7 to accumulate into the nucleolus, where rDNA transcription takes place, providing an opportunity for E7 to interact with nucleolar proteins involved in this process. GST-pull down and co-immunoprecipitation assays showed interactions between p14ARF, UBF1 and E7, although p14ARF and E7 are not able to directly interact. Co-expression of a pRb-binding-deficient mutant (E7C24G) and p14ARF resulted in EC24G nucleolar accumulation, but not in a significant higher activation of rDNA transcription, suggesting that the inactivation of pRb is involved in this phenomenon. Thus, p14ARF fails to prevent E7-mediated UBF1 phosphorylation, but could facilitate nucleolar pRb inactivation by targeting E7 to the nucleolus. While others have reported that p19ARF, the mouse homologue of p14ARF, inhibits some functions of E7, we showed that E7 inhibits a p53-independent function of p14ARF. These results point to a mutually functional interaction between p14ARF and E7 that might partly explain why the sustained p14ARF expression observed in most cervical pre-malignant lesions and malignancies may be ineffective.